2022
DOI: 10.1002/dad2.12277
|View full text |Cite
|
Sign up to set email alerts
|

Verbal fluency response times predict incident cognitive impairment

Abstract: Introduction In recent decades, researchers have defined novel methods for scoring verbal fluency tasks. In this work, we evaluate novel scores based on speed of word responses. Methods We transcribed verbal fluency recordings from 641 cases of incident cognitive impairment (ICI) and matched controls, all participants in a large national epidemiological study. Timing measurements of utterances were used to calculate a speed score for each recording. Traditional raw and speed scores were entered into Cox propor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 52 publications
1
7
0
Order By: Relevance
“…Similarly, “pause length” (ignoring intervals shorter than 250 ms) contributes to machine learning regression models predicting scores on the Mini-Mental State Exam ( Folstein and Folstein, 1975 ) and Clinical Dementia Rating ( Morris, 1993 ) sum of boxes ( Linz et al, 2017 ). In other work on the same data set analyzed here, we observed that the speed of word generation during verbal fluency improves estimates of time to ICI ( Ayers et al, 2022 ). However, the speed scores we investigated previously incorporated all word generation times rather than separating transitions into those between linked words (which we term “edge” transitions) and those between unlinked words (“switch” transitions), as we do in these analyses.…”
Section: Introductionsupporting
confidence: 63%
See 1 more Smart Citation
“…Similarly, “pause length” (ignoring intervals shorter than 250 ms) contributes to machine learning regression models predicting scores on the Mini-Mental State Exam ( Folstein and Folstein, 1975 ) and Clinical Dementia Rating ( Morris, 1993 ) sum of boxes ( Linz et al, 2017 ). In other work on the same data set analyzed here, we observed that the speed of word generation during verbal fluency improves estimates of time to ICI ( Ayers et al, 2022 ). However, the speed scores we investigated previously incorporated all word generation times rather than separating transitions into those between linked words (which we term “edge” transitions) and those between unlinked words (“switch” transitions), as we do in these analyses.…”
Section: Introductionsupporting
confidence: 63%
“…This observation holds true, especially for our “progressive” group. We have argued elsewhere that this group is likely to consist mainly of individuals with AD, while the acute group is likely to contain individuals with other pathologies (e.g., vascular disease or Lewy body diseases) as well as individuals with AD, albeit at an earlier stage of disease ( Ayers et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…In previous work, we found that scores based on speed of word generation were more informative than raw scores for predicting onset of cognitive impairment from semantic fluency, 48 especially in the subset of individuals most likely to have AD. However, in the current analysis, we do not find that amyloid positivity is associated with identically derived speed scores for the RAVLT.…”
Section: Discussionmentioning
confidence: 85%
“…If a participant fails to recall any words, the stopping time is equal to 1. Division by zero is not an issue as the total duration for a task is never zero seconds. A speed score was calculated as in previous work on verbal fluency 47,48 . Briefly, the entire set of inter‐word intervals (i.e., durations between valid words) is subjected to a sequence of three transformations: first, by taking the 4th root to mitigate positive skew, second, normalizing the values to lie between 0 and 1, and third, subtracting from 1.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation